Legal Protection of Artificial Intelligence Applications in Banking - Maheswara Perbawa Sukawati; Amad Sudiro; I Wayan Gde Wiryawan (Contrarius Indonesia, 2025)
The rapid development of Artificial Intelligence (AI) in Indonesia’s banking sector has transformed traditional financial services into digital-based systems that emphasize speed, efficiency, and accessibility. However, this transformation presents significant legal and ethical challenges related to data security, algorithmic accountability, and consumer protection. This study analyzes the legal framework governing AI implementation in Indonesian banking, focusing on the Financial Sector Development and Strengthening Law, the Personal Data Protection Law, the Electronic Information and Transactions Law, and the regulatory role of Bank Indonesia and the Financial Services Authority. The research employs a normative legal approach supported by limited empirical insights, combining statutory, case, comparative, and historical analyses. The findings reveal regulatory fragmentation and a legal vacuum concerning liability for AI-related losses, particularly in cases of algorithmic error and data breaches. In contrast, comparative studies of Japan and the European Union show the necessity of establishing AI governance based on transparency, accountability, and proportional liability. Therefore, Indonesia urgently requires a specific legal framework that integrates ethical, human-centered, and risk-based principles to ensure data security, protect consumer rights, and promote trustworthy AI implementation in the financial sector.